(untitled) (Research, Society and Development, 2020)
Objective: To analyze the occupational risks that interfere in the health and quality of life of nurses and users and the preventive actions developed by this professional in their daily work, in the hospital environment.Method: Exploratory and descriptive study, with a qualitative approach, carried out with 13 nurses from a University Hospital in the south of Rio Grande do Sul. For data collection, a semi-structured interview guide was used. The data were recorded, transcribed and analyzed through thematic analysis. Results: The most prominent accident risks in the nurse’s work were those directly related to user care. The most evident ones were biological, ergonomic and psychological. Conclusion: In the prevention of health risks in the hospital environment, it is necessary to emphasize educational actions of a permanent nature, in order to make it possible to recognize situations that cause risk and learn preventive actions. It is emphasized that the adoption of safe behaviors, anchored in biosafety measures they are fundamental strategies in the prevention and promotion of the health of workers, users and family members in the hospital environment.